The Impact of Emotion-Based Teaching Strategies on Motivation in Collaborative Learning - G. P. MacAllister (Journal of Advanced Research in Education, 2025)
This paper explores the role of EBTS in enhancing motivation within collaborative learning environments in Canada’s multicultural and inclusive educational landscape. Drawing from psychological frameworks such as Deci and Ryan’s SDT and Pekrun’s Control-Value Theory, the study delves into how emotions shape motivation, engagement, and academic success. The paper emphasizes the interplay between positive emotions, such as curiosity and pride, and essential psychological needs, including autonomy, competence, and relatedness, which are critical to sustaining intrinsic motivation. It examines the impact of emotions on group dynamics, highlighting the benefits of fostering trust, empathy, and respect in collaborative settings. Empirical evidence from Canadian classrooms demonstrates the transformative potential of EBTS in promoting student participation, resilience, and inclusivity. The findings underscore the need for integrating emotional engagement into pedagogical practices to enhance both individual and collective learning outcomes. By addressing emotional dimensions, educators can create enriched, culturally responsive, and motivating learning environments that prepare students for academic and interpersonal success.